PENGEMBANGAN PROGRAM UNGGULAN DI LEMBAGA PENDIDIKAN ISLAM - Hani’atul Khoiroh (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2020)
Abstract: The essence of an education is to make humans mature, foster personality (personality) and a sense of responsibility. This kind of education has meaning, namely mental, moral and physical (body) training that results in high-cultured human beings to carry out their duties and responsibilities as servants of God. Because of this, it is appropriate that all educational potential should be directed towards achieving a quality level of educational progress, namely by developing a series of excellent programs that must be managed professionally. This article would like to explain the concept of a superior program and its theoretical foundation, in addition to that the writer also explains the principles and strategies that must be taken to develop excellent programs in Islamic educational institutions, which are then implemented in order to create superior and quality human beings.Keywords: Development programs, Islamic Education and Institutions